Enlarging the Immunities of European Parliament’s Members: The Junqueras Judgment - Torre de Silva, Victor (Cambridge University Press, 2021)
Members of Parliament have traditionally enjoyed different kinds of immunities; nowadays, these are openly criticized on several grounds. The Court of Justice of the European Union (CJEU) has recently given a judgment on the inviolability of European Parliament’s members, which might be regarded as a milestone in its scarce case law on the matter: Oriol Junqueras Vies, Judgment of the Grand Chamber of December 19, 2019. This Article intends to summarize and comment on this decision, a preliminary reference requested by the Spanish Supreme Court in a notorious criminal procedure, connected with the suspended referendum on Catalonia’s independence. The CJEU reinforces the inviolability of Members of European Parliament (MEPs), thus strengthening the powers of this institution. However, the judgment perhaps fails to fully capture European Court of Human Rights (ECtHR) case law and was rendered at a time when the controversy on Mr. Junqueras had arguably become outdated.
Keywords: European Parliament; Immunities; Inviolability; European Court of Justice; Preliminary ruling; 72 Filosofía; ODS 16 - Paz, justicia e instituciones sólidas